The Origin Of Electric Charge And Its Relation To Closed And Open Strings In The Early Universe - McGraw Jr., David (JOURNAL OF ADVANCES IN PHYSICS, 2025)
The C-Neutralino, a particle of immense significance, is the primary particle that drives the beginning of our universe. The C-Neutralino decays into other particles, including protons and electrons. The C-Neutralino existed before the beginning of time. They were the catalyst for the start of our universe. As the C-Neutralinos start to collide in the early universe, temperatures rise. When temperatures become as hot 10100 degrees celsus our universe gets its start. We understand this as the Big Bang that happened at the beginning of our universe. The electric charge starts in the early universe during the first few minutes. The first moments after the Big Bang are called the quark-gluon plasma phase. In this phase, there are two different periods. The first period occurs right after the beginnings of the universe. The temperatures are so hot during the first few minutes that the quarks and gluons are strings. The top quark and the antibottom quark are strings during this time in the early universe. As they collide, they start to spin, oscillate, and rotate, becoming one quark. This heavy quark called the cd-quark, was responsible for developing electric charges in the early universe. This change in mass of the cd-quark is the true origin of electric charges. Electric charge is not mass dependent on mass amount but on mass change in the early universe. Charged particles have finite lifetimes. They are not stable like other particles.